Analisis Iklim untuk Perencanaan Media Tanam yang Mampu Beradaptasi dalam Dampak Perubahan Iklim - Sugiarto, Ari; Syafriyandi, Debby; Yovanda, Ridho (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Sugiarto, A., Syafriyandi, D., & Yovanda, R. (2024). climate analysis for planting media planning that is adaptable to the impact of climate change. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 753–761). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The aimed of this research was to analyze the climat for planning the development of planting media designs that are able to adapt to the impacts of climate change. The climate crisis seriously impacts the agricultural sector, such as the threat of flooding and drought. As a form of adaptation to the impact of climate change, the agricultural sector must innovate, one of which is through planting media. It is essential to develop planting media based on climate analysis to provide an excellent opportunity for successful adaptation to the impact of climate change. Climate analysis in a place to support the development of planting media can include analysis of trends in climate variables and estimates of changes in the water balance. Changes in climate variables and estimates of changes in the water balance provide information for the development of planting media designs in an area to avoid the impacts of flooding and drought. Changes in climate variables can provide detailed information on future environmental conditions and changes in plants' availability and needs of water. Specifically, the development of planting media designs can be a determinant of the success of adaptation to the impacts of climate change that are being faced, but planting media designs must be considered based on the results of climate analysis.